2014
DOI: 10.1080/01904167.2014.888739
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Mineralization from Sugarcane Vinasse

Abstract: 2 Vinasse is a liquid residue applied as a fertilizer in sugarcane crops. However, in areas far away from sugarcane mills the cost of the distribution can be very high due, the large volume of water. So, one solution is to concentrate the vinasse by the evaporation process to reduce transport costs. Considering that the nitrogen mineralization kinetics is not known in concentrated vinasse, the objective of this study was to evaluate the net and potential nitrogen mineralization in soil that received vinasse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The results revealed that the rice productivity increases with the combined application of chemical fertilizers and organic amendments (Table 2). This improvement might be associated with nutrient availability through organics ((da Silva et al, 2014;Soni et al, 2014). Besides, the organics might be the source of slow nutrient release that optimizes their availability throughout the rice growth period ( (Kalaivanan and Omar Hattab, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the rice productivity increases with the combined application of chemical fertilizers and organic amendments (Table 2). This improvement might be associated with nutrient availability through organics ((da Silva et al, 2014;Soni et al, 2014). Besides, the organics might be the source of slow nutrient release that optimizes their availability throughout the rice growth period ( (Kalaivanan and Omar Hattab, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Crushing of 100 kg sugarcane results in 3 kg of PM production as a by-product (Kalaivanan and Omar Hattab, 2016). Ethanol production from cane industries gives rise to another by-product known as sugarcane vinasse (SV), processing of 1-liter ethanol produces about 10-15 liters of SV (Da Silva et al, 2014). Utilization of these by-products in the agricultural sector as an organic source of fertilization can help to reduce chemical fertilization, resolve to dispose of issues of by-products and improve the farmer's income (Sarwar et al, 2008;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The assigned fertilizers of the respective group featured a high N content, and thus revealed a low C to N ratio. Hence, commercial organic fertilizers of animal and plant origins provided a high amount of plant available N [35][36][37][38]. The N fractions in most commercial organic fertilizers are mainly comprised of uniform and relatively pure substances, such as keratin, blood proteins, or plant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of soil pH results predominately in: (i) a reduction of cation exchange capacity decreasing the ability of the soil to retain nutrients in cation forms, that are then prone to leaching, (ii) an inhibition of soil biological processes which have significant cascading effects on transformations of nutrients, especially N, (iii) an induction of nutrient precipitation (e.g., P), (iv) a reduction of nutrient uptake by plant roots [12,13]. These effects, however, might be mitigated, since the decomposition of stillage organic matter, including transformations of organic anions, the reactions of ligand exchange, as well as ammonification and denitrification of nitrogen compounds, potentially increase soil pH [7,14]. It should be emphasized that available literature data on the use of stillage for fertilizer purposes refers mainly to molasses stillage [3,7,14], and the studies carried out under field conditions have had a rather limited scope [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…These effects, however, might be mitigated, since the decomposition of stillage organic matter, including transformations of organic anions, the reactions of ligand exchange, as well as ammonification and denitrification of nitrogen compounds, potentially increase soil pH [7,14]. It should be emphasized that available literature data on the use of stillage for fertilizer purposes refers mainly to molasses stillage [3,7,14], and the studies carried out under field conditions have had a rather limited scope [2,7].…”
Section: Introductionmentioning
confidence: 99%